Building Secure, Concurrent, Distributed DBaaS with Confidential Data over Threshold Access Structure (International Journal of Engineering and Computer Science, 2015)
In a cloud, Guaranteeing confidentiality within the Database as a service (DBaaS) paradigm remains a problem. Here, we propose ConfidentialConcurrenttoSecureDBaas with some modifications to produce availability, security, accessibility and reliability without exposing unencrypted information to the cloud provider.  It additionally permits multiple, freelance and regionally distributed clients to execute synchronal operations on encrypted data by eliminating the need for intermediate server between the cloud consumer and also the cloud provider; to preserve data confidentiality and consistency at the client and cloud level; To achieve this, ConfidentialConcurrentAccessToDBaaS integrates existing cryptographic schemes, isolation mechanisms, and novel strategies for management of encrypted metadata on the untrusted cloud database.